Analisis Service Quality di Puskesmas X Surabaya dengan Quality Function Deployment - Puspandam Katias; Fuji Rahayu (UNUSA Press, 2018)
Abstract: As a health service provider under the management of the Surabaya City Government, the puskesmas (community health center) which is the unit of analysis is committed to improving and maintaining the services provided to its customers. In this study, the integration of service quality methods is used by measuring the perception gap and expectations of servqual measurement results which then design customer satisfaction performance through quality function deployment, the application of the combination of the two methods is expected to contribute to the improvement of puskesmas performance. The results of the study are expected to be able to objectively find the gap of each dimension of servqual and provide recommendations from the analysis of quality function deployment.